MED12 regulates a transcriptional network of calcium-handling genes in the heart - Kedryn K. Baskin; Catherine A. Makarewich; Susan M. DeLeon; Wenduo Ye; Beibei Chen; Nadine Beetz; Heinrich Schrewe; Rhonda Bassel-Duby; Eric N. Olson (JCI Insight, 2017)
The Mediator complex regulates gene transcription by linking basal transcriptional machinery with DNA-bound transcription factors. The activity of the Mediator complex is mainly controlled by a kinase submodule that is composed of 4 proteins, including MED12. Although ubiquitously expressed, Mediator subunits can differentially regulate gene expression in a tissue-specific manner. Here, we report that MED12 is required for normal cardiac function, such that mice with conditional cardiac-specific deletion of MED12 display progressive dilated cardiomyopathy. Loss of MED12 perturbs expression of calcium-handling genes in the heart, consequently altering calcium cycling in cardiomyocytes and disrupting cardiac electrical activity. We identified transcription factors that regulate expression of calcium-handling genes that are downregulated in the heart in the absence of MED12, and we found that MED12 localizes to transcription factor consensus sequences within calcium-handling genes. We showed that MED12 interacts with one such transcription factor, MEF2, in cardiomyocytes and that MED12 and MEF2 co-occupy promoters of calcium-handling genes. Furthermore, we demonstrated that MED12 enhances MEF2 transcriptional activity and that overexpression of both increases expression of calcium-handling genes in cardiomyocytes. Our data support a role for MED12 as a coordinator of transcription through MEF2 and other transcription factors. We conclude that MED12 is a regulator of a network of calcium-handling genes, consequently mediating contractility in the mammalian heart.